ENERGY POLICIES: RURAL ELECTRIFICATION IN PERU AND ITS IMPACT ON SOCIOECONOMIC DEVELOPMENT IN THE AREA OF HIDRANDINA S. A. 2007-2016 - Bambaren Miasta, Manuel (2021)
This research has the general objectiveidentify energy development policies inrural electrification that relate to the developmentsocioeconomic in the concession area (La Libertadand Cajamarca) of the company Hidrandina S.A., period2007-2016. An investigation was carried outcorrelational; its level was descriptive; its design, notexperimental correlational transactional type;Likewise, the hypothetical-deductive method was used,for an essential feature of hypotheses is thatmust be “falsifiable”, that is, they must have one or morelogically incompatible circumstances. For this oneThe study investigated 800,027 people, including managers,officials and clients of the concession area (La Libertadand Cajamarca) of the company Hidrandina S.A. The sampleoptimal was made up of 384 people, who wererandomly selected. For the study,observation techniques were used, they were classified andpertinent events were recorded in accordanceto the subject under investigation. The survey was applied to thedirectors, officials and clients of the concession area(La Libertad and Cajamarca). It was concluded that, according to the level of correlation between the variables obtainedin the study of Pearson's correlation, it was avalue of 0.7911, which indicates that there is a high level ofcorrelation between energy development policiesand socioeconomic development in the concession area(La Libertad and Cajamarca) of the company HidrandinaS.A., period 2007-2016.